Determinants of load capacity factor in an emerging economy: The role of green energy consumption and technological innovation - Liu, Xuan; Olanrewaju, Victoria Olushola; Agyekum, Ephraim Bonah; El-Naggar, Mohamed F.; Alrashed, Mohammed M.; Kamel, Salah (Frontiers in Environmental Science, 2022)
The fast rise of technological innovations and anthropogenic activities has resulted in numerous negative environmental impacts affecting environmental quality. As a result, this research employed a holistic indicator called the “load capacity factor” to assess environmental quality derived from two major ecological elements: ecological footprints and bio-capacity. There is insufficient information in the available literature to investigate the variables influencing the load capacity factor in the context of ecological quality. The study employed dynamic autoregressive distributed lag (DYARDL) and spectral causality approaches to explore the influence of fossil fuel, technological innovation, and renewable energy usage in improving South Africa’s load capacity factor. The DYARDL results show that economic expansion and fossil fuel energy lessens environmental quality while renewable energy boosts environmental sustainability. Furthermore, the spectral causality shows that fossil fuel, renewable energy usage, and economic growth can forecast load capacity factor in the long-term. Overall, the findings suggest that renewable energy is critical for reaching long-term environmental targets and inhibits the fossil fuels usage in the energy mix. We urge South Africa to embrace empirical evidence and implement long-term measures to reduce ecological damage to create a more sustainable environment.